2018
DOI: 10.1111/aec.12576
|View full text |Cite
|
Sign up to set email alerts
|

Dendrochronological analyses and climatic signals of Alchornea triplinervia in subtropical forest of southern Brazil

Abstract: The predominance of secondary forest-species in Brazilian subtropical forests highlights the importance of understanding the ecology of these taxa, and dendrochronology provides valuable information about the growth and climate response of tree species. The wide distribution of Alchornea triplinervia (Spreng.) Mull. Arg. (Euphorbiaceae), and the presence of growth rings in its wood, leds to its selection for this study. Samples were collected from 34 trees growing in rainy dense forest fragments in the cities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
2
8
1
Order By: Relevance
“…Distinct growth rings had already been recorded in subtropical species in southern Brazil (Oliveira et al 2009;Spathelf et al 2010;Shimamoto et al 2015;Andreacci et al 2017;Kanieski et al 2017;Reis-Ávila & Oliveira 2017;Granato-Souza et al 2018;Blagitz et al 2019). In this study, distinct growth rings were also observed in most studied species, being absent only in C. sylvestris, C. canjerana and E. argentinum.…”
Section: Discussionsupporting
confidence: 78%
“…Distinct growth rings had already been recorded in subtropical species in southern Brazil (Oliveira et al 2009;Spathelf et al 2010;Shimamoto et al 2015;Andreacci et al 2017;Kanieski et al 2017;Reis-Ávila & Oliveira 2017;Granato-Souza et al 2018;Blagitz et al 2019). In this study, distinct growth rings were also observed in most studied species, being absent only in C. sylvestris, C. canjerana and E. argentinum.…”
Section: Discussionsupporting
confidence: 78%
“…Dendrochronological studies developed in the Amazonian floodplains also showed a negative correlation between ring width and the amount of precipitation and flood pulse during the vegetation period (Schongart et al 2004). In Brazil, with the exception of the ecosystems investigated by Schongart et al (2004), other studies in tropical climate showed strong influence of precipitation in the radial growth (Callado & Guimarães 2010;Brandes et al 2011;Latorraca et al 2015;Locosselli et al 2016b;Souza et al 2016;Granato-Souza et al 2019;Vasconcellos et al 2019), whereas negative correlations are more often in subtropical climate (Oliveira et al 2010;Andreacci & Botosso 2014;Perone et al 2016;Kanieski 2017;Granato-Souza et al 2018a;b). As in L. bahiana, a study carried out with Chukrasia tabularis A. Juss.…”
Section: Dendrochronologymentioning
confidence: 96%
“…3A). In studies investigating the relationships between tree growth and climate in the Brazilian Atlantic Forest, this parameter varied from 0.20 up to 0.69 (Dünisch 2005;Oliveira et al 2010;Venegas-González et al 2016;Fontana et al 2018a;Granato-Souza et al 2018a;. Thus, by comparison, the L. bahiana chronology has a median correlation considering the forest pattern.…”
Section: Dendrochronologymentioning
confidence: 99%
“…Such a relationship that can be observed in tropical ecosystems with the use of dendrochronology [11,13,14]. Climate signals such as precipitation (e.g., rain, mist, fog and cloud water), temperature and/or droughts regulate the growth of TMCFs' tree species [15,16]. Dendroecology allows us to identify climatic processes across time and can be used to reconstruct past local and regional climates [9,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Climate signals such as precipitation (e.g., rain, mist, fog and cloud water), temperature and/or droughts regulate the growth of TMCFs' tree species [15,16]. Dendroecology allows us to identify climatic processes across time and can be used to reconstruct past local and regional climates [9,16,17]. In this context, one of the most important advances in dendrochronological studies has been the additional focus on anatomical features such as vessel traits and/or tree-ring anatomy [13,18,19].…”
Section: Introductionmentioning
confidence: 99%